Why Jury Duty Matters : A Citizen's Guide to Constitutional Action - Ferguson, Andrew G. (Book collections on Project MUSE., 2013)
Every year, thousands of American citizens are summoned for the important civic duty of serving on a jury. What is their role, why is it a duty, and why is it so important? This book is addressed to a lay audience. It will be useful for those citizens who have served on juries, for those who will someday be called to serve, and, indeed, for anyone who has an inquisitive mind about a crucial part of our legal system. The author describes the history of the jury and explains why juries play such a critical role in the contemporary American system of justice. -- Provided by publisher.